(untitled) (Actual Problems of Psychology in Educational Institutions, 2018)
The article is devoted to the problem of the formation of mental activities in student age The essence of the definition of "mental actions" in the article is presented domestic psychology. An attempt is made to determine the polarity structures of mental actions. It emphasizes the role of mental activity in the process assimilation of educational material. The dynamics and main types are determined mental actions in the course of comprehension of scientific information. Specifics are revealed the functioning of mental activities in the conditions of studying at universities. Presented the results of the empirical study of the level of development of mental activity in students